A place to hang the moon ebook - Albus, Kate (2021)
A heartwarming story about three siblings, evacuated from London to live in the countryside, looking for a permanent home—and a new meaning for family. A New York Public Library Best Book of the Year It is 1940 and William, 12, Edmund, 11, and Anna, 9, aren't terribly upset by the death of the not-so-grandmotherly grandmother who has taken care of them since their parents died. But the children do need a guardian, and in the dark days of World War II London, those are in short supply, especially if they hope to stay together. Could the mass wartime evacuation of children from London to the countryside be the answer? It's a preposterous plan, but off they go— keeping their predicament a secret, and hoping to be placed in a temporary home that ends up lasting forever. Moving from one billet to another, the children suffer the cruel trickery of foster brothers, the cold realities of outdoor toilets and the hollowness of empty stomachs. But at least they find comfort in the village lending library— a cozy shelter from the harshness of everyday life, filled with favorite stories and the quiet company of Nora Müller, the kind librarian.  The children wonder if Nora could be the family they've been searching for. . . . But the shadow of the war, and the unknown whereaouts of Nora's German husband complicate matters.  A Place to Hang the Moon is a story about the importance of family: the one you're given, and the one you choose. Filled with rich, sensory prose, allusions to classic children's stories like A Little Princess, Mary Poppins, and The Story of Ferdinand , this cozy tale with a classic feel is sure to warm your heart. Don't miss Kate Albus's Nothing Else But Miracles which takes place in New York City during WWII and was described as "historical fiction at its finest" in a starred review from School Library Journal. An ALSC Notable Children's Book An SCBWI Crystal Kite Award Winner A Junior Library Guild Gold Standard Selection Named to the Pennsylvania Young Readers Choice List A CCBC Choice